Baseline Parameters for Rotational Thromboelastometry (ROTEM) in Healthy Women Undergoing Elective Cesarean Delivery: A Prospective Observational Study in Australia. Issue 1 (March 2020) - Lee, J.; Eley, V.A.; Wyssusek, K.H.; Coonan, E.; Way, M.; Cohen, J.; Rowell, J.; van Zundert, A.A.
Abstract : ( Int J Obst Anesth . 2019;38:10–18) Hypercoagulation is a physiologic change associated with pregnancy. Despite this hypercoagulable state, obstetric hemorrhage is a leading cause of maternal morbidity and mortality worldwide. Management of obstetric hemorrhage can be optimized by utilizing point-of-care ROTEM testing. However, normal reference ranges for ROTEM have not been established specifically for the obstetric population. Often ROTEM reference ranges obtained from the nonpregnant population have been utilized when using this testing in the obstetric population. The aim of this study was to establish baseline parameters for ROTEM in normal pregnancy. A secondary aim of the study was to compare these values with the reference ranges reported by the manufacturer, based on studies in nonpregnant patients.